Fitrah Penampilan Diri (Studi Mengenai Anjuran Mencabut Bulu Ketiak) - Zikriadi; Abustani Ilyas; Mahmuddin (Jurnal Ilmu Pendidikan dan Sosial, 2023)
This research discusses the nature of self-appearance or (personal grooming) which contains suggestions, one of which is to remove armpit hair. This research is included in a literature review, the object of this study is hadiths related to personal grooming, the approach used is maqasid al-shari'ah al-syatibi. The results of the study reveal that self-appearance is part of aesthetics and in Islam it is included in adab or ethics as part of the sunnahs of human nature. The benefits of shaving the armpit hair are cleanliness and health, so removing it is a sunnah and is liked.